2004
DOI: 10.1088/0953-2048/17/9/023
|View full text |Cite
|
Sign up to set email alerts
|

Low field AC susceptibility of YBCO: the frequency and field dependence of intra- and intergrain coupling losses in the absence of vortices

Abstract: The AC susceptibility (χ + iχ ) of YBCO with and without intergrain coupling was measured in AC fields within 0.13 and 3.72 mT and frequencies from 20 Hz to 12.8 kHz. Intergrain coupling was eliminated by dispersing the powder in insulating varnish. For the coupled and uncoupled grains, the χ (T ) transition near T C is field independent, indicating that the fields used do not drive the sample into the mixed state. Thus, the χ and χ curves cannot be associated with vortex motion. In χ (T ), a peak near T C due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
4
9
0
Order By: Relevance
“…The graphene nanoparticles can be a powerful material to act as an as effective pinning center. These findings were supported from the previous studies that had also reported that graphene/carbon base nanomaterials addition could be beneficial, especially in the Y123 superconductor performance [24,36,49,50]. However, further improvements of the Y123 superconducting performance are possible in order to obtain more higher of J cm values.…”
Section: Ac Susceptibility Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…The graphene nanoparticles can be a powerful material to act as an as effective pinning center. These findings were supported from the previous studies that had also reported that graphene/carbon base nanomaterials addition could be beneficial, especially in the Y123 superconductor performance [24,36,49,50]. However, further improvements of the Y123 superconducting performance are possible in order to obtain more higher of J cm values.…”
Section: Ac Susceptibility Analysissupporting
confidence: 86%
“…However, T p is broadened and shifted to the lower temperature with the increase of graphene nanoparticles in Y123 samples due to the weakening of intergranular coupling between grains, as shown in Figure 4 [48]. This decrement may be due to some defects at the grain boundaries such as grain disorientation, twin boundaries and vacancies that can act as weak links, therefore disturbing the T p and pinning forces [49]. The broad width of χ" might also be caused by the second superconducting transition of the secondary phase.…”
Section: Ac Susceptibility Analysismentioning
confidence: 97%
“…Figures6 and 7show the measured temperature dependencies of χ and χ for the polycrystalline and single crystal samples, respectively.The field strength at the sample site was calibrated using the same Texas Instruments DRV5055A2 Hall effect sensor described in section 2.4. As shown in figure4, the field strength is set by both the amplitude of the signal generator output and the value of the series resistance R.The polycrystalline measurements of figure6are qualitatively consistent with the results reported by Nikolo and others using more sophisticated apparatuses[9,15,16]. The temperature dependence of χ exhibits an inflection point at a temperature T * just below the superconducting transition temperature.…”
supporting
confidence: 87%
“…However, the transition starts to broaden at x = 0.8 and x = 1.0, suggesting that x = 0.4 is the optimum weight percentage for SnO 2 addition. This broadened curve is caused by the magnetic flux penetrating the sample surface when there is a decrease in the screening current required to exclude the flux [30]. From T c-onset and the phase-lock in the temperature, T cj , tabulated in Table 3, maximum Josephson current, I 0 , can be estimated using the Ambegaokar-Baratoff theory in the following equation [31], I0=(1.57 ×108 A/K) Tc-onset2Tc-onset Tcj…”
Section: Resultsmentioning
confidence: 99%